Quantitative online survey of self-perceived knowledge and knowledge gaps of medicines research and development among Finnish general public - Tran Minh Mirjami; Tamminen Manu; Tamminen-Sirkiä Jenni; Majumder Mamun Majumder; Tabassum Rubina; Lahti Tuuli (BMJ PUBLISHING GROUP, 2022)
Objectives This study explored self-reported knowledge and interest to learn more about medicines research, development and health technology assessment among Finnish general public. It also aimed to define possible knowledge gaps and needs for public education regarding these topics.
Design Online survey with 503 participants. The questionnaire was originally developed as a part of the Needs Assessment Work Package of the European Patients’ Academy on Therapeutic Innovation Project. The survey was carried out in Finland in 2019.
Methods The survey was conducted as an online survey by Kantar TNS Gallup Forum online panel. The data were analysed by using the freely available programming language R. Relationships between the demographic characteristics (such as age, gender and education level) of respondents and their knowledge or interest in medicines research and development were determined using Pearson’s χ2 tests. Statistically significant responses of demographic characteristics in the respondents’ knowledge or interest in medicines research were determined by logistic regression.
Results Of the 503 respondents (age 16–64) only 12% reported having good or very good knowledge of medicines research and development in general. Regarding health technology assessment, pharmacoeconomics and regulation, the percentage of respondents reporting good or very good knowledge was as low as 8%. Respondents were most interested in learning more about predictive and personalised medicine (47%) and least interested in medicines regulation (30%) and pharmacoeconomics (31%).
Conclusions Self-reported knowledge about medicines research and development and health technology assessment appears to be very low in Finland. Patient and public participation is recognised as an important and essential element in up-to-date medical research and assessment of new treatments. In order to participate as an active and equal partner in these processes, the public needs more information and education in these topics.